Research Capacity Building for Learning Development of Student Teachers Using Results-Based Monitoring and Evaluation and Results-Based Management - Varasunun, Pinda (Ratchaphruek Journal, 2026)
The objectives of this study were to: 1) Develop a research capacity building process to enhance the learning of student teachers using results-based monitoring and evaluation and results-based management; and 2) Investigate the outcomes of research capacity building for learning development within five evaluation dimensions: relevance, effectiveness, efficiency, impact, and sustainability. The population consisted of fourth-year student teachers in Mathematics Education, Faculty of Education and Development Sciences, during the academic years 2022-2023. The research instruments included operational manuals, tests, questionnaires, and interview forms. Data were analyzed by mean, percentages, and content analysis. The findings revealed that: 1) The process of developing research capacity to enhance the learning of student teachers using results-based monitoring and evaluation and results-based management consists of five key components: inputs, processes, outputs, outcomes, and impacts. The evaluation of the process using connoisseurship technique revealed that, in terms of accuracy, suitability, feasibility, and utility were rated at the highest level. 2) The evaluation of research capacity building showed that the dimensions of relevance, effectiveness, efficiency, and sustainability achieved all target indicators. However, within the impact dimension, two indicators did not meet the expected outcomes: dissemination of research findings and utilization of research results at the organizational level.